Evaluation of Particulate matter and air pollutants level in the ambient air of Bengaluru city - Sangeetha , MD; Nagaraja, Sharath Burugina; Sreenath, Menon PK (Indian Journal of Community Health, 2024)
Background: Air pollution has been a global environmental concern, and its effects on human health in the past have played an important role. Thus, this study investigated the concentrations of particulate matter (PM10, PM2.5), nitrogen dioxide (NO2), sulfur dioxide (SO2), and carbon monoxide (CO) in four distinct areas of Bengaluru over one year. Materials and Methods: It is a descriptive cross-sectional design, utilizing secondary data from the Central Pollution Control Board's National Air Quality Monitoring Programme. Data analysis was conducted using SPSS software, expressing descriptive statistics such as mean, standard deviation, and maximum concentrations. Results: The study reveals varying air quality levels, with PM10 peaking at 102 µg/m³ in Silk Broad (August 2023) and NO2 spiking in February 2023. SO2 peaks at Majestic (March 2023), while CO poses health risks, peaking in January 2023. Silk Broad shows highest PM10; Majestic has elevated NO2, SO2, and CO. Conclusion: The study reveals fluctuating air quality, with PM10 peaking at 102 µg/m³ in Silk Broad station (August 2023) and NO2 spiking in February 2023. SO2 and CO levels also vary, posing health risks, particularly at Majestic station. Regional disparities highlight the need for targeted pollution control.